2020
DOI: 10.1074/mcp.ra120.002059
|View full text |Cite
|
Sign up to set email alerts
|

The Aspergillus fumigatus Secretome Alters the Proteome of Pseudomonas aeruginosa to Stimulate Bacterial Growth: Implications for Co-infection

Abstract: Individuals with cystic fibrosis are susceptible to co-infection by Aspergillus fumigatus and Pseudomonas aeruginosa. Despite the persistence of A.  fumigatus in the cystic fibrosis lung P. aeruginosa eventually predominates as the primary pathogen. Several factors are likely to facilitate P. aeruginosa colonization in the airways, including alterations to the microbial environment. The cystic fibrosis airways are hypoxic, nitrate-rich environment, and the sputum has higher amino acid concentrations than norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 72 publications
(93 reference statements)
0
27
2
Order By: Relevance
“…While there is an emphasis on the inhibition of A. fumigatus by P. aeruginosa , in the study by Briard et al, it was found that some bacterial volatile compounds could actually stimulate fungal growth [ 47 ]. Recently, a study reported that the secretome of A. fumigatus stimulates bacterial growth by altering the P. aeruginosa proteome [ 48 ].…”
Section: Implications Of Bfis On Microbial Fitnessmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is an emphasis on the inhibition of A. fumigatus by P. aeruginosa , in the study by Briard et al, it was found that some bacterial volatile compounds could actually stimulate fungal growth [ 47 ]. Recently, a study reported that the secretome of A. fumigatus stimulates bacterial growth by altering the P. aeruginosa proteome [ 48 ].…”
Section: Implications Of Bfis On Microbial Fitnessmentioning
confidence: 99%
“…Numerous reports of MHB isolation, identification, and studies on their consequences exist [ 49 , 50 , 51 , 52 , 53 ]. The roles of MHB in symbiosis, their effects on arbuscular mycorrhizal or ectomycorrhizal host, and their specificities and mechanisms have been studied for decades and have been reviewed extensively elsewhere [ 46 , 47 , 48 ]. Such tri-partite interactions help promote plant growth as well as stress tolerance [ 47 , 54 , 55 , 56 ].…”
Section: Implications Of Bfis On Host Health and Diseasementioning
confidence: 99%
“…For example, P. aeruginosa can inhibit the growth of A. fumigatus conidia, but not of preformed hyphae [ 17 ]. This may be attributed to the ability of hyphae, but not conidia to produce gliotoxin which has anti- Pseudomonas activity [ 100 , 113 ]. A. fumigatus produce hydroxamate-containing siderophores (ferricrocin, hydroxyferricrocin, fusarinine C, triacetylfusarinine C) in response to iron limitation.…”
Section: The Interactions Between a Fumigatus mentioning
confidence: 99%
“…How these enzymes directly or indirectly influence bacterial growth has not yet been investigated in detail, however, recent studies have shown that A. fumigatus alters the environmental conditions in vitro, by converting a nutrient-poor, nitrate-rich environment into one rich in amino acids. These conditions, known to exist in the CF airways, may enable P. aeruginosa to outcompete A. fumigatus by promoting a metabolic-driven increase in bacterial growth [ 113 ]. Analysis of the culture filtrates produced by A. fumigatus identified an abundance of degradative enzymes which are also involved in virulence, including alkaline protease 1, alkaline protease 2, aspergillopepsin-1, and major allergen Asp f 2 [ 115 , 117 , 118 , 119 ].…”
Section: The Interactions Between a Fumigatus mentioning
confidence: 99%
“…A. fumigatus response to iron is also modulated by a pseudomonal quorum sensing molecule, P. aeruginosa quinolone signal, which enhances fungal growth and metabolism under iron-rich conditions, similar to those found in the CF lung environment [ 138 ]. Conversely, recent proteomic analysis by Margalit et al has shown that A. fumigatus can confer fitness to P. aeruginosa by increasing environmental nutrient availability, especially of amino acids and nitrate, which thereby stimulates bacterial growth and pathogenicity [ 139 ]. The nature of A. fumigatus-P. aeruginosa interactions becomes more complicated when other factors are considered.…”
Section: Combined Infection With Aspergillus Fumigatus mentioning
confidence: 99%